First World War in Literature: Reflections across the Genres - Upadhyay, Hriseekesh (Literary Studies, 2015)
War is a major theme in literature from ancient times to the contemporary world. Lyrics, ballads, tales, stories, all kinds of poetry and fictions, philosophical reflections and intellectual analyses have been composed and written about war all over the world in all periods of history. War is the result of conflicting human action and desire, too often it results out of atrocities and inhumanities and wrongful action or desire of one person or group of persons against others. War on many occasions in the long history of mankind has been the only option to salvage one’s dignity and enforce right order and values in society and community of nations and organized groups. In this sense war has proved the most important redress for restoring values, justice and dignity among right-minded people. The First World War that began raging in summer a century ago across the frontiers of Europe to cause havoc to much of the world in subsequent four years bears many features of this characterization.